5x+3(8-x)=4x-2(8+x)

Simple and best practice solution for 5x+3(8-x)=4x-2(8+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+3(8-x)=4x-2(8+x) equation:



5x+3(8-x)=4x-2(8+x)
We move all terms to the left:
5x+3(8-x)-(4x-2(8+x))=0
We add all the numbers together, and all the variables
5x+3(-1x+8)-(4x-2(x+8))=0
We multiply parentheses
5x-3x-(4x-2(x+8))+24=0
We calculate terms in parentheses: -(4x-2(x+8)), so:
4x-2(x+8)
We multiply parentheses
4x-2x-16
We add all the numbers together, and all the variables
2x-16
Back to the equation:
-(2x-16)
We add all the numbers together, and all the variables
2x-(2x-16)+24=0
We get rid of parentheses
2x-2x+16+24=0
We add all the numbers together, and all the variables
40!=0
There is no solution for this equation

See similar equations:

| 8/5(z−6)=−1/5(2z+3) | | 3t+4=3t+2+6 | | 24-2x=18+2x | | d−5−3=−4 | | 41=2b-7 | | x-(-4)=26 | | 6/27=x/9 | | 30x-10+5x+40=100 | | x+2+4x-6+4x-4=46 | | M^2-28=-3m | | -1/3*4+z=-5/6 | | 5x+3(x-10)=4(2x-6) | | 5x-25=155 | | 2(n+2)+3(n-3)=-20 | | 10-3(m-2)=40 | | 10^x*10^2=640 | | x/9+8=-3x+2 | | -7(x-3)=2x-33 | | 4v-13-10=12-24v+5 | | 3d+4=6d−11 | | b=8.2 | | 6/27=x9 | | -4p=92 | | 2x+5=8x−7 | | (7x-6)+(3x-5)=(8x+19) | | 7(x-5)+5(x-2)=3(x+3)-2(x+2) | | 13g=-1300 | | (21x-70)= | | (2x+20)+(3x+10)+90=180 | | -4(2x-4)=4x=2(3x-1) | | 5^8x=7^x-3 | | F÷-2/3=-1/3f= |

Equations solver categories